Percepciones de los pacientes sobre infecciones relacionadas con la atención de la salud y medidas de seguridad - De Paiva, Miriam Cristina Marques da Silva [UNESP]; Gallasch, Cristiane Helena; Lima, Silvana Andrea Molina [UNESP]; Sitton-Kent, Lucy; Devi, Reena; Xyrichis, Andreas (Universidade de Estado do Rio de Janeiro, 2017)
Objectives: to analyze data from qualitative studies of patient perceptions of measures to prevent and control healthcare-related infections and factors that contribute to their own safety. Method: systematic review of publications from 2006 to 2016, followed by thematic synthesis by coding patients’ accounts and interpretations of findings given. Results: six themes highlighted barriers to patients’ participating actively in promoting their own safety: insufficient information supply; poor comprehension; negative feelings; negative experiences; behavior of health care personnel; and factors that influence patient involvement. Conclusion: the gap between patients’ understanding infection prevention and control measures and their becoming involved in the process point to a need for measures to foster effective communication, better care personnel-patient relations, and access to information that encourages patients to interact and contribute to health care.
Percepções de pacientes sobre infecções relacionadas à assistência à saúde e medidas de segurança
Patients’ perceptions of health care-related infections and safety measures
Keywords: Active patient participation; Cross infection; Health promotion; Patient safety